Central bank reserves and interbank market liquidity in the euro area - Beaupain, Renaud; Durré, Alain (Journal of Financial Intermediation, 2013)
The market-oriented approach promoted by the European Central Bank in the design of its refinancing operations creates incentives to credit institutions to use actively the interbank market to manage their liquidity needs. In this context, we examine the ability of the overnight segment to guarantee the timely provision of unsecured funds to banks to smoothly absorb their liquidity shocks. This paper specifically focuses on the speed of reversion of transaction costs and available depth to their equilibrium levels in this market for overnight unsecured funds. The reported evidence points to time-varying liquidity adjustments and identifies liquidity, market activity and the institutional setting of the ECB’s refinancing operations as significant determinants of the observed resiliency regimes. Our analysis also shows how the speed of mean reversion of market liquidity, by affecting the level and the volatility of the overnight market rate, also affects the anchoring of the yield curve in the euro area.